Open Loop Saddle Point on Linear Quadratic Stochastic Differential Games (Communications in Mathematical Research, 2021)
In this paper, we deal with one kind of two-player zero-sum linearquadratic stochastic differential game problem. We give the existence of an openloop saddle point if and only if the lower and upper values exist.
Keywords: stochastic differential game; saddle point; open loop strategy.